Environmental, social and governance, and earnings management - Panjaitan, David Willyam; Eddy Suranta (Jurnal Ekonomi, 2024)
This study aims to examine the relationship between Environmental, Social Governance, and earning management  to determine the difference in earning management  among companies that have ESG scores and prove ESG differences between companies that have ESG scores. Many people think that earnings management is an act of fraud. This literature study explains and describes the problem from an outside perspective of earnings management. This article compares CSR scores in the years studied to see whether companies are focused on building CSR. The theory used in this study is legitimacy theory, where companies that have ESG scores are considered as companies that have a good reputation; the study population is all companies that have ESG scores, and the sample used by companies is all manufacturing companies (20 publicly traded companies reporting ESG) that have ESG scores. All hypotheses tested using SPSS 24. Pengujian hipotesis pertama di uji dengan uji korelasi, pengujian hipotesis kedua dengan menggunakan uji kruskal wallis. Hasil penelitan selanjutnya membuktikan bahwa ada hubungan antara ESG score dengan manajemen laba. Selain itu membuktikan bahwa ada perbedan anatar ESG score yang ada di perusahan. Companies that have a high score minimize risk by implementing earnings management.